Analisa Ketebalan Kayu Bulian Terhadap Densitas Film Sebagai Kemampuan Serapan Kayu Bulian Terhadap Radiasi Analisa Ketebalan Kayu Bulian Terhadap Densitas Film Sebagai Kemampuan Serapan Kayu Bulian Terhadap Radiasi - Oktavia Puspita Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
In Indonesia, various types of wood show potential as radiation shielding materials, particularly those with sufficient hardness to substitute for lead (Pb). Bulian wood (Eusideroxylon zwageri), commonly known as ironwood, is one of the strongest species from the Sumatran forest. It is highly durable, resistant to termites, insect attacks, environmental fluctuations, and even seawater. Given these properties, studying its radiation absorption capacity is essential to assess its feasibility as a lead substitute in radiation shielding. This research investigates the absorption capacity of Bulian wood at varying thicknesses and analyzes its density equivalence on film compared to lead sheets. The study employed a quantitative, experimental method conducted in the Radiography Laboratory of the Faculty of Vocational Studies, Baiturrahmah University. Film density was measured at each thickness variation of Bulian wood, corresponding to levels on the step wedge. Data were processed using bivariate analysis to determine correlations between Bulian wood thickness and lead sheet equivalence. The results revealed a p-value of 0.00 (p < 0.05), indicating rejection of the null hypothesis and acceptance of the alternative. A significant relationship was observed between 25 cm thick Bulian wood and 2 mm thick lead, suggesting their film density values are equivalent.